Plagiatul între încălcarea unei norme penale sau a uneia de drept administrativ // Plagiarism between the violation of a criminal law or an administrative law - Carmen Adriana Domocoş (Analele Ştiinţifice ale Universităţii "Al.I. Cuza" din Iaşi. Ştiinţe Juridice, 2024)
Law no. 206/2004, regarding good conduct in scientific research, technological development and innovation, with subsequent amendments and additions, in wich the tern of „plagiarism” is legally identified, does not sanction or prohibit the taking over, in itself, of texts, expressions, ideas, demonstrations, data, hypotheses, theories, results or scientific methods, because such a ban would be equivalent to the impossibility of carrying out any research activity. What is sanctioned by Law no. 206/2004 is the taking over of these elements, from previous works published by another author or by the same author, without citation, by indicating the name of the author, the title, the publisher, the year of publication and the page/pages from which the takeover was made. In a case analysed in the current article, the plaintif was accused of deviations from the obligation to respect the ethics and deontology of the research activity, consisting of the identical takeover in ch. IV of one's own doctoral thesis of texts from another previously published scientific work, in violation of the citation rules set forth above. For deviations from good conduct in research and development, the disciplinary sanctions provided for in the Code of ethics and professional deontology of research and development personnel are applied, as well as the sanctions provided for in Law no. 64/1991 on patents, republished, with subsequent amendments, in Law no. 129/1992 regarding the protection of industrial designs and models, republished, and in Law no. 8/1996 on copyright and related rights, with subsequent amendments and additions.